Interlocking of Grain in Indian Timbers - Limaye, V. D. (Indian Forester, 1954)
Interlocking of grain to a smaller or greater extent is a characteristic of a majority of Indian wood species. Grain has been described so far from experience of working with the timbers. An attempt has been made in this Bulletin to measure the deviation of grain and divide the species into seven groups as a step towards standardization of descriptions of wood species.